GEOMETRIC CONCEPTS IN JAMBI BATIK: DEVELOPING A HYPOTHETICAL LEARNING TRAJECTORY FOR REFLECTION MATERIAL - Zalsi, Rona Naila; Pasaribu, Feri Tiona; Gustiningsi, Tria (Universitas Cokroaminoto Palopo, 2025)
Learning geometric transformations often presents challenges for students due to their abstract nature and limited connection to real-world contexts. Reflection is one of the most difficult concepts for students to understand. This study aims to design a Hypothetical Learning Trajectory (HLT) for geometric reflection using the PMRI approach through the context of Batik Jambi. This research employed a design research approach in the preliminary design phase, with data co llected through teacher interviews and literature studies. The result is a five-stage HLT design that utilizes the Bungo Melati motif as a symmetry context, guiding students from concrete experiences toward formal understanding through progressive mathematization. The findings indicate that incorporating the Batik Jambi context can enhance students’ comprehension of reflection while also connecting mathematics learning with local cultural values. This HLT design has the potential to serve as a foundation for developing a Local Instructional Theory (LIT) for more meaningful and contextualized geometry learning.